Speed Sensor-less Control of Induction Motor based on Super-helical Sliding Mold - An, Xiaoyu; Ren, Chenglong; Guo, Leilei; Jia, Lianhui; Sun, Zhihong; Mei, Yongxiang; Wang, Haoyu (Recent Patents on Engineering, 2025)
BackgroundWith the continuous progress of technology and the development of shield enterprises, higher requirements are put forward for speed estimation and system stability in the sensorless control system of induction motors in shield machines.MethodsIn order to solve the problems of velocity observation error and sliding mode vibration of the induction motor velocity observation method based on sliding mold observer, an improved super-helical sliding mold observer is proposed by combining the currently known invention patents and the information based on the induction motor control.ResultsThe open square of the current error value is introduced into the continuous function of the sliding variable of the observer, and two different functions are used in the boundary layer to replace the sign function, which reduces the sliding mode noise and vibration problems, and the stability of the observer is proved by the Lyapunov stability theory. After that, a phase-locked loop alternative model-referenced adaptive algorithm is used as the rotational speed observation link, which solves the problem that the conventional model-referenced adaptive algorithm relies on the current-modeled magnetic chain observer.ConclusionThe improved super-helical sliding mode observer and phase-locked loop control method effectively reduce the system vibration and speed estimation error of the motor under different speeds and loading conditions, and the observed currents are smoother, which improves the stability of the system. Simulation and experimental results under different working conditions show the effectiveness of the proposed method.
Keywords: Sensorless control